Time-Course Transcriptome Analysis of Gingiva-Derived Mesenchymal Stem Cells Reveals That Fusobacterium nucleatum Triggers Oncogene Expression in the Process of Cell Differentiation - Kang, Wenyan; Sun, Tianyong; Tang, Di; Zhou, Jiannan; Feng, Qiang (Frontiers in Cell and Developmental Biology, 2020)
Fusobacterium nucleatum (F. nucleatum) has pathogenic effects on oral squamous cell carcinoma and colon cancer, while the effects of continuously altered gene expression in normal human cells, as induced by persistent exposure to F. nucleatum, remain unclear. In this study, a microarray Significant Profiles (maSigPro) analysis was used to obtain the transcriptome profile of gingiva-derived mesenchymal stem cells (GMSCs) stimulated by F. nucleatum for 3, 7, 14 and 21 d, and the results revealed 790 (9 clusters) differentially expressed genes (DEGs), which were significantly enriched in cell adherens junction and cancer-related pathways. On the basis of short time-series expression miner (STEM) analysis, all the expressed genes in the GMSCs were grouped into 50 clusters according to dynamic gene expression patterns, and the expression levels of 3 gene clusters in the F. nucleatum-treated GMSCs were significantly different than the predicted values. Among the 790 DEGs, fifty tumor-associated genes (TAGs; such as L3MBTL4, CD163, CCCND2, CADM1, BCL7A, and IGF1) and 5 core dynamic DEGs (PLCG2, CHI3L2, L3MBTL4, SH2D2A, and NLRP3) were identified during F. nucleatum stimulation. Results from a GeneMANIA database analysis showed that PLCG2, CHI3L2, SH2D2A and NLRP3 and 20 other proteins formed a complex network, of which, 12 genes were enriched in cancer-related pathways. Based on the 5 core dynamic DEGs, the related microRNAs (miRNAs) and transcription factors (TFs) were obtained from public resources, and an integrated network composed of the related TFs, miRNAs, and mRNAs was constructed. The results indicated that these genes were regulated by several miRNAs, such as miR-372-3p, miR-603 and miR-495-3p, and several TFs, including CREB3, GATA2 and SOX4. Our study suggests that long-term stimulation by F. nucleatum may trigger the expression of cancer-related genes in normal gingiva-derived stem cells.